Word order in Qumran Aramaic - Chandler, Edward H (ProQuest Dissertations & Theses, 2005)
Aramaic was one of the most widely used languages of the ancient Near East. Although most of the Dead Sea Scrolls from Qumran are written in Hebrew, a small number use a variety of Aramaic. All of Qumran Aramaic (QA) has reached published form, though a few minor manuscripts have yet to appear in an authoritative edition. Each manuscript has been subjected to some level of paleographic, morphological, phonological, and lexicographical study. Though there are a few attempts to account for all of QA in preliminary “grammar” form, one gap that this dissertation seeks to fill is in the area of QA word order: specifically, unmarked word orders and the rationale for various marked word orders. From manuscripts whose Qumran provenance is certain or generally accepted, we have identified 745 usable clauses that attest two or more constituents. Many clauses have discernible contexts, though not all of them. Our aim in this study is twofold: to account for all attested word orders and to account for the writers' rationales for using a given word order in a given context. We have approached this problem using modern linguistic principles, primarily applying the insights of Functional Sentence Perspective and Benveniste's genre distinction; and secondarily applying aspects of generative theory. We are in substantial agreement with the readings and translations of the editions. The few passages on which we registered exceptions are noted in the final chapter. In narrative, QA prefers VSO order in unmarked contexts, only departing from this is in parallel and subordinate clauses. Discourse shows variation in word order, though first-person narration also prefers VSO. Much of the discourse variation occurs in apocalyptic contexts, raising the possibility of the influence of Daniel. In both genres, pronominalized constituents tend to move in front of the subject. Subject fronting is found in utterance-initial, paragraph-initial, and circumstantial clauses. Fronted objects appear to be topical, though the data set is limited. Verbless clauses show a tendency toward SP word order in unmarked contexts. A relative word order freedom in verbless subordinate clauses may be accounted for by the marking provided by QA's sizable inventory of subordinating conjunctions.